Support structure-catalyst electroactivity relation for oxygen reduction reaction on platinum supported by two-dimensional titanium carbide. (January 2021) - Lee, Yeongdae; Ahn, Jang Hyuk; Park, Hee-Young; Jung, Jeawoo; Jeon, Yuju; Lee, Dong-Gyu; Kim, Min-Ho; Lee, Eunryeol; Kim, Chanseok; Kwon, Youngkook; Lee, Hyun-Wook; Jang, Jong Hyun; et al.
Abstract: It is demonstrated that the electroactivity of the oxygen reduction reaction (ORR) of Pt depends on the structure of a support. Highly conductive two-dimensional titanium carbide (Ti3 C2 ) was selected as the support for Pt because of the expected strong metal-support interaction (SMSI) between Pt and Ti. To control the edge-to-basal ratio, the number of Ti3 C2 layers was modulated by exfoliation. Pt nanoparticles (4 nm) were loaded on three different Ti3 C2 supports including multi-, few-, and mono-layered Ti3 C2 (22L-, 4L-, and 1L-Ti3 C2, respectively). The edge-to-basal ratio of layered Ti3 C2 increased as the number of layers increased. The edge-dominant support (22L-Ti3 C2 ) donated more electrons to Pt than the basal-dominant supports (4L-Ti3 C2 and 1L-Ti3 C2 ). As a result, electron-rich Pt with less d-band vacancies (e.g., Pt/22L-Ti3 C2 ) showed higher ORR activity. In addition, the electron transfer from the support to Pt inducing the strong interaction between Pt and Ti improved the durability of the ORR electroactivity of Pt. Graphical abstract: Image 1 Highlights: Effects of the support structure-activity relationship on ORR were demonstrated. Pt was deposited on edge-dominant Ti3C2 to basal-dominant Ti3C2. Edge-dominant Ti3C2 donates more electrons to Pt compared to basal-dominant Ti3C2. Electron-rich Pt on edge-dominant Ti3C2 shows superior activity and stability.